2009
DOI: 10.2337/dc08-1453
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal LDIflare but Normal Quantitative Sensory Testing and Dermal Nerve Fiber Density in Patients with Painful Diabetic Neuropathy

Abstract: OBJECTIVE -Abnormal small nerve fiber function may be an early feature of diabetic neuropathy and may also underlie painful symptoms. Methods for assessing small-fiber damage include quantitative sensory testing (QST) and determining intraepidermal nerve fiber density. We recently described a reproducible physiological technique, the LDIflare, which assesses small-fiber function and thus may reflect early dysfunction before structural damage. The value of this technique in painful neuropathy was assessed by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 25 publications
6
47
1
1
Order By: Relevance
“…Furthermore, although LDImax was similarly reduced in the MV− and MV+ groups, the LDIflare in the MV− group was greater and not significantly different from that in the control group; this would not expected if LDIflare was related to LDImax. Finally, as with our previous studies, there was no correlation between LDImax and LDIflare, confirming that they measure different physiological variables and are not influenced by each other within the range of microvascular blood flow studied [3,9,10]. LDImax represents the maximum vasodilatory capacity.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Furthermore, although LDImax was similarly reduced in the MV− and MV+ groups, the LDIflare in the MV− group was greater and not significantly different from that in the control group; this would not expected if LDIflare was related to LDImax. Finally, as with our previous studies, there was no correlation between LDImax and LDIflare, confirming that they measure different physiological variables and are not influenced by each other within the range of microvascular blood flow studied [3,9,10]. LDImax represents the maximum vasodilatory capacity.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, in idiopathic painful peripheral neuropathy, a condition primarily affecting small nerve fibres, metabolic dysregulation has been implicated [7,8]. In support of these observations, we have recently demonstrated impaired C-fibre function in individuals with type 2 diabetes free from clinical neuropathy and in individuals with IGT using a relatively new method, the laser Doppler imager flare (LDIflare) technique [3,9,10]. This involves heating the skin on the dorsum of the foot to 44°C and measuring the size of the axon-reflex-mediated flare using a laser Doppler imager (LDI).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…QST, microneurography, and autonomic testing such as laser Doppler-induced flare reactions have been utilized to detect SFN, and advances in human in vivo imaging have demonstrated corneal innervation to be another potential site of monitoring SFN [15,47,52,57]. However, because QST is dependent upon subjective feedback, autonomic dysregulation may have origins in sensory neuropathy, and microneurography and corneal imaging are still largely experimental, cutaneous skin biopsy with direct measures of small-caliber axons provides a definitive diagnosis of SFN [45, 46, 48, 58•].…”
Section: Diagnosismentioning
confidence: 99%
“…As with IENFD and CCM, LDIflare has been validated against large and small fiber markers and bears a strong correlation to IENFD (r = 0.77, p < 0.001) [62]. It can detect abnormal small fiber function in increasing severity of diabetic neuropathy [64][65], impaired glucose tolerance with normal thermal thresholds [26], and as reported recently, in non-diabetic nonneuropathic individuals with hypertriglyceridemia [66]. Studies have shown that glycemic control and HbA1c have a strong relationship with LDIflare results [67][68].…”
Section: Methods For Assessment Of Small Fiber Neuropathymentioning
confidence: 99%